IS ONE LANGUAGE ENOUGH FOR YOU? - Musurmonova, Mohinur Shodmonovna (INTERNATIONAL CONFERENCES, 2023)
Firstly, since the beginning of life there have been more than 7,100 languages what decorates the world. Unfortunately, due to several reasons some of them are less widely used than others. It can be due to globalization, world wars and all over unity of countries via study, business. Despite this, the world languages are temporary. That’s why, they are changed after a period such as Russian language. The study gained insight into the question that how much people are likely to learn a second language. Especially, which is assumed to be the future world language. And, which is worth spending time. The study findings suggest that in order to develop carrier in later life we should have knowledge about this.